2008
DOI: 10.1073/pnas.0711129105
|View full text |Cite
|
Sign up to set email alerts
|

Temperature increase of 21st century mitigation scenarios

Abstract: Estimates of 21st Century global-mean surface temperature increase have generally been based on scenarios that do not include climate policies. Newly developed multigas mitigation scenarios, based on a wide range of modeling approaches and socioeconomic assumptions, now allow the assessment of possible impacts of climate policies on projected warming ranges. This article assesses the atmospheric CO 2 concentrations, radiative forcing, and temperature increase for these new scenarios using two reducedcomplexity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(93 citation statements)
references
References 33 publications
3
90
0
Order By: Relevance
“…This is an inconsistent comparison, however, because actions to reduce CO 2 emissions will also result in reductions in methane and pollutant emissions because of many common sources of these emissions (18,25).…”
Section: Discussionmentioning
confidence: 99%
“…This is an inconsistent comparison, however, because actions to reduce CO 2 emissions will also result in reductions in methane and pollutant emissions because of many common sources of these emissions (18,25).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have indeed shown that this is the case 7,8,18,19 , at least for peak warming and monotonously increasing cumulative carbon emissions. If a set carbon budget limit is exceeded, CO 2 needs to be removed actively from the atmosphere afterwards [20][21][22] to bring emissions back to within the budget.…”
Section: The Purpose Of Budgetsmentioning
confidence: 97%
“…If one considers pathways to climate stabilization, such as recently given in the reference concentration pathways (RCPs) [30,31], then it is clear that continuing updates of the GWP could have quite significant implications in the future. Along the RCP3 pathway, which is aimed at stabilizing global warming at 2 • C, the methane GWP would increase by about 33 per cent as the concentration of methane decreased to about 65 per cent of present-day levels, and CO 2 stabilized at levels about 10 per cent higher than its present-day levels.…”
Section: Issues With Global Warming Potentialsmentioning
confidence: 99%
“…Emission scenarios consistent with achieving climate stabilization have been developed in some detail [30,31], but changes in the emissions of different greenhouse gases that keep to the same total GWP-weighted emissions do not keep to the same RF over time. For example, if technological development led to faster reduction in methane emissions and there was a GWP-based compensating increase in CO 2 emissions, then the result would be inconsistent with climate stabilization.…”
Section: Comparing Greenhouse Gases For Stabilization Scenariosmentioning
confidence: 99%